Teologi Lingkungan dalam Kearifan Lokal Masyarakat Sunda - Ujang Suyatman (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2018)
The environmental crisis created by human activity in the modern era has threatened the existence of planet earth and the lives of various creatures in it. These problems are not adequately addressed by scientific technology and methods alone, but a strategy that can fundamentally and radically change the way people view and behave towards their environment. This study examines the principles of Islamic teachings and their implementation in local wisdom practices of the Sundanese people, as one of the strategies for the development of morals and the way of view of human beings towards nature and the environment.